FENOMENA KAWIN KONTRAK DAN PROSTITUSI â€˜DAWARâ€™ DI KAWASAN PUNCAK BOGOR - Wahab, Abdul Jamil; Kustini, Kustini; Ali, Muchtar (Al Qalam, 2018)
The beauty of nature in Cisarua Puncak sub-district of Bogor Regency has been recognized by the Arab travellers for a long. Many of them were coming to this sub-district for a tour. It has both positive and negarive effects. Their presence leads to the growth of local economy, but on the other hand, it also leads to the emergence of marriages contract. Even, a changing trends is founds there, a trend what is known as a hidden prostitution and this practice has become disturbing. This qualitative research was conducted to elaborate the phenomenon of contract marriages practice and prostitution in Cisarua Puncak sub-district of Bogor Regency, stratted from the history, the process, the actors, and the community and local authorities response. This research also analyzed the violations of law and indications of crimilan acts. The research result succeded to describe a detail information of the phenomen of marriages contract and â€œdawarâ€ protitution. The research also concluded that the marriage contract and its derivates, namely â€œdawarâ€ prostitution, is a violation of religion norm and law. But admittedly, its really no easy to directly eradicated, but it could be disciplined gradualy. The recommendation of the research are: legal and religious aproach are strongly necessary; economic approach also needed by doing skill trainings for those who involved in contract marriage and â€œdawarâ€ prostitution. So they will have any competences and opportunities to work in legal fields.